MOVIE CLIPS AS A MEDIA TO TEACHING WRITING OF NARRATIVE TEXTS - Anisa Oktaviani; Dedeh Rohayati (Universitas Galuh, 2021)
This paper reports on student’s perception on the effect of teaching writing of narrative texts using media movie clips. Movie clip is one kind of audio visual media which is very useful in teaching learning process if the teacher carefully prepares it and then she/he uses it effectively to support the explanation of the lesson.This research uses mixed method design with explanatory type design by means of three data collection techniques : pre test and post test, document test, and interview. The sample of this research was 12 students of ten grade from one Vocational High School in Tasikmalaya. The result of this research shows the significant effect with normality test is 0.63≥ 0.05 so that H0 is accepted. Then value of pretest comes from populations that are normally distributed, and that significant value of post test is 0.15 ≥0.05, so that H0 is accepted. The improvement made by movie clips is an avarage pretest amounting 63.58 and 77.5 for posttest. It means that there is an improvement, and the perception obtained from interview shows a lot of positive comment. Meanwhile, each student has different scores, high and low, that are able to influence how their learning achievement are in the classroom, but they have the same goal in writing class in that they want to write well and correctly. Before writing, they must also have good exercise and skill in order to get correct writing results and to achieve success in this course.Keywords: mixed method. movie clips, writing